Data Center Room Monitoring Based on Temperature and Humidity with Internet of Things - Rizkiawan, M. Asep; Ramza, Harry; Nuroji, Nuroji; Sofwan, Agus (Jambura Journal of Electrical and Electronics Engineering, 2024)
The idea of the Internet of Things (IoT) encompasses the application of technologies such as sensors and software to an object for the purpose of communicating, controlling, connecting, and exchanging data with other devices while connected to the Internet. In this study, the IoT concept developed was used to monitor and regulate conditions within the data center. The development method used is the life cycle method of system development. The development process involved modifying the Arduino Uno with an esp8266 microcontroller and a DHT-22 sensor to detect temperature and humidity in real time. The testing of IoT development was done using the black box and white box methods. Research results show that the prototyped IoT network can operate well and successfully improve data center performance. In addition, users can also access the system through websites and mobile applications to facilitate the monitoring process.